If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.6(x + 100) + 0.4x = 85 Reorder the terms: 0.6(100 + x) + 0.4x = 85 (100 * 0.6 + x * 0.6) + 0.4x = 85 (60 + 0.6x) + 0.4x = 85 Combine like terms: 0.6x + 0.4x = 1x 60 + 1x = 85 Solving 60 + 1x = 85 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + 1x = 85 + -60 Combine like terms: 60 + -60 = 0 0 + 1x = 85 + -60 1x = 85 + -60 Combine like terms: 85 + -60 = 25 1x = 25 Divide each side by '1'. x = 25 Simplifying x = 25
| 4s+2s-6=6 | | 7x+18=-2(x-18) | | -11/20=x-13/16 | | -11=14+x | | 4x+3=22x | | 2x-13=8-6x+3 | | 2(4x+3)=5(3x+4) | | x(5x+21)+18=0 | | 5p-100=x | | 84-7x=11x+20 | | 2(5x+8)=3(4x-2) | | 2x+19=9x-44 | | 9+2.7t=4.8t-9 | | 8x-3y=-24 | | x-4+99=8 | | 4-7x=3x+1 | | 3x+47=7x+10 | | 12x-24-8x=-6x+16 | | 5x+13-4x=7+4x-6 | | 3x+14=85-8x | | 1/4=z+7/4 | | 14x+120+10x=360 | | 3[6x-4]=-52 | | 4+7(-12+x)=-38 | | 24+14x=x | | 3y+z=am | | [6x-4]=-52 | | 4x-10=6x+12 | | 14x+24=x | | 6x-4=-52 | | 6x-7=5x+6 | | 8x-1=8x-x |